Expression of exo‐inulinase gene from Aspergillus niger 12 in E. coli strain Rosetta‐gami B (DE3) and its characterization. (26th February 2016) - Yedahalli, Shreyas S.; Rehmann, Lars; Bassi, Amarjeet
Abstract : Inulin is a linear carbohydrate polymer of fructose subunits (2‐60) with terminal glucose units, produced as carbon storage in selected plants. It cannot directly be taken up by most microorganisms due to its large size, unless prior hydrolysis through inulinase enzymes occurs. The hydrolyzed inulin can be taken up by microbes and/or recovered and used industrially for the production of high fructose syrup, inulo‐oligosaccharides, biofuel, and nutraceuticals. Cell‐free enzymatic hydrolysis would be desirable for industrial applications, hence the recombinant expression, purification and characterization of an Aspergillus niger derived exo‐inulinase was investigated in this study. The eukaroyototic exo‐inulinase of Aspergillus niger 12 has been expressed, for the first time, in an E. coli strain [Rosetta‐gami B (DE3)]. The molecular weight of recombinant exo‐inulinase was estimated to be ∼81 kDa. The values of K m and V max of the recombinant exo‐inulinase toward inulin were 5.3 ± 1.1 mM and 402.1 ± 53.1 µmol min −1  mg −1 protein, respectively. Towards sucrose the corresponding values were 12.20 ± 1.6 mM and 902.8 ± 40.2 µmol min −1  mg −1 protein towards sucrose. The S/I ratio was 2.24 ± 0.7, which is in the range of native inulinase. The optimum temperature and pH of the recombinant exo‐inulinase towards inulin was 55°C and 5.0, while they were 50°C and 5.5 towards sucrose. The recombinant exo‐inulinase activity towards inulin was enhanced by Cu 2+ and reduced by Fe 2+, while its activity towards sucrose was enhanced by Co 2+ and reduced by Zn 2+ . © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:629–637, 2016